The Night Window - Koontz, Dean R. 1945- (Dean Ray); Rodgers, Elisabeth S. (Grand Haven, MI : Brilliance Audio, Inc., 2019)
Since her sensational debut in The Silent Corner, listeners have been riveted by Jane Hawk's resolute quest to take down the influential architects of an accelerating operation to control every level of society via an army of mind-altered citizens. At first, only Jane stood against the 'Arcadian' conspirators, but slowly others have emerged to stand with her, even as there are troubling signs that the 'adjusted' people are beginning to spin viciously out of control. Now, in the thrilling, climactic showdown that will decide America's future, Jane will require all her resources, and more, as she confronts those at the malevolent, impregnable center of power.
Keywords: Hawk, Jane -- (Fictitious character) -- Fiction; Fugitives from justice -- Fiction; Government investigators -- Fiction; Secret societies -- Fiction; Conspiracies -- Fiction; Audiobooks; Psychological fiction; Thrillers (Fiction); Novels